Design of an Exoskeleton Prototype for Shoulder Rehabilitation - Sosa Méndez, D; Arias Montiel, M; Lugo González, E (Revista Mexicana de Ingenieria Biomedica, 2017)
The motor disability is a problem at the global level and according to the census 2010 from INEGI, in Mexico, people with mobility problems represent 58.3 % of the population with disabilities. To face this problem, robotic devices for rehabilitation have emerged which allow to perform therapies with accuracy, efficiency, reduction of physical efforts and the opportunity to perform them in group. However, these devices may not match the mobility of the members to rehabilitate and their adaptation to the mexican anthropometry is limited. In this article, the design of an exoskeleton focused on the Mexican adult population with partial loss of mobility in the shoulder is presented. The objective is to develop an exoskeleton capable of generating the 3 basic movements of the shoulder (flexion-extension, abduction-adduction and internal-external rotation) considering the anthropometric measurements of the target population. For the design of the prototype, an adaptation of the mechatronic design methodology for robots is used. The proposed design is validated kinematically through numerical simulations in Matlab® and ADAMS™, the numerical results prove the range of mobility of each exoskeleton joint. Moreover, a finite element analysis is carried out to quantify the stress and strain levels in the exoskeleton, verifying the selection of materials for its manufacture.